Michelle Walker in conversation with Jerome Carson. Issue 2 (21st March 2019) - Walker, Michelle; Carson, Jerome
Abstract : Purpose: The purpose of this paper is to provide a profile of Michelle Walker. Design/methodology/approach: In this single case study, Michelle gives a short background to the development of her depression and is then interviewed by Jerome. Findings: Michelle sets out the reasons she developed depression. These map onto the research conducted by Brown and Harris some 50 years ago, showing how social factors can create a vulnerability to develop depression. Research limitations/implications: Single case studies provide us with one person's narrative. That narrative is, however, unique and can often offer us insights that are lost in large statistical surveys. Practical implications: Michelle found that the Cognitive Behaviour Therapy (CBT) approach really helped her. However, she should never have had to wait as long as she did for that help. Mental health services must respond quickly, even if only to offer a triage assessment. Social implications: Brown and Harris identified four key vulnerability factors for depression in women. Michelle met three of these. How many other women are in a similar situation and are suffering in silence? Originality/value: We can learn a lot from the factors that helped Michelle recover from her depressive episode: medication, CBT, the support of her mother, education, finding her soulmate and, although she does not say it, her own rugged determination and personal resilience.